2018
DOI: 10.1088/1758-5090/aae75a
|View full text |Cite
|
Sign up to set email alerts
|

StarPEG/heparin-hydrogel based in vivo engineering of stable bizonal cartilage with a calcified bottom layer

Abstract: Repaired cartilage tissue lacks the typical zonal structure of healthy native cartilage needed for appropriate function. Current grafts for treatment of full thickness cartilage defects focus primarily on a nonzonal design and this may be a reason why inferior nonzonal regeneration tissue developed in vivo. No biomaterial-based solutions have been developed so far to induce a proper zonal architecture into a non-mineralized and a calcified cartilage layer. The objective was to grow bizonal cartilage with a cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Zonal designs mimicking the vertical organization of cells and matrix in a joint are promising tools to enhance cartilage regeneration. Several studies have shown that not only are such designs technically feasible [17,18] but that they can improve integration into osteochondral defects [14,19,20]. The importance of the calcified cartilage has already been depicted in 1975 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonal designs mimicking the vertical organization of cells and matrix in a joint are promising tools to enhance cartilage regeneration. Several studies have shown that not only are such designs technically feasible [17,18] but that they can improve integration into osteochondral defects [14,19,20]. The importance of the calcified cartilage has already been depicted in 1975 [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared a zonal construct consisting of two layers with two different cell types to a non-zonal design for cartilage regeneration. We hypothesized that the zonal approach would facilitate integration [18,24,25,26] into the defects and would result in a more natural tissue when compared to a non-zonal design and to empty control defects. After six months in vivo, zonal and non-zonal constructs showed a significantly increased bone loss in the defects when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of cartilage tissue engineering, several different approaches exist that try to produce cartilage constructs with zones similar to the native structure. Such zones are, for example, defined by the use of different cells (zone-specific chondrocytes, MSCs) [ 26 , 27 , 28 ] or different material properties (stiffness gradients, different hydrogels) [ 29 , 30 , 31 , 32 ]. The combination of ACPCs in a superficial layer and MSCs in a bottom layer has been tested in other hydrogels with encouraging results [ 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, strong promotors may be able to drive overexpression also in the pellet center, in spite of an inappropriate microenvironment, but this would not add to our understanding of the natural mechanisms of MPC hypertrophy we are searching for, since expression of downstream targets like IHH and IBSP may also depend on the richer microenvironment. Thus, we propose that further understanding of the here-described 3D phenomena of chondrocyte hypertrophy requires new models and techniques that combine forced target gene expression with exposure to critical microenvironmental cues like this is possible by layered cartilage tissue design and layered tissue mineralization in transwells (Kunisch et al, 2018).…”
Section: Discussionmentioning
confidence: 99%